2023
DOI: 10.34133/research.0031
|View full text |Cite
|
Sign up to set email alerts
|

Alternative Copper-Based Single-Atom Nanozyme with Superior Multienzyme Activities and NIR-II Responsiveness to Fight against Deep Tissue Infections

Abstract: Nanozymes are considered to represent a new era of antibacterial agents, while their antibacterial efficiency is limited by the increasing tissue depth of infection. To address this issue, here, we report a copper and silk fibroin (Cu-SF) complex strategy to synthesize alternative copper single-atom nanozymes (SAzymes) with atomically dispersed copper sites anchored on ultrathin 2D porous N-doped carbon nanosheets (CuN x -CNS) and tunable N coordination numbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 40 publications
0
31
0
Order By: Relevance
“…Previous studies have demonstrated that the catalytic activity of a Cu-based single atom catalyst depends on the N coordination number of the Cu atom. 50 More recently, Bai et al 51 developed Cu-based SAzymes with an adjustable N coordination number by pyrolyzing Cu–silk fibroin complexes. The authors found that CuN x –CNS SAzymes with a CuN 4 structure exhibited superior multienzyme activity (POD-, OXD- and CAT-like) than those with a CuN 2 structure.…”
Section: Non-noble Metal Single Atom Nanozymesmentioning
confidence: 99%
“…Previous studies have demonstrated that the catalytic activity of a Cu-based single atom catalyst depends on the N coordination number of the Cu atom. 50 More recently, Bai et al 51 developed Cu-based SAzymes with an adjustable N coordination number by pyrolyzing Cu–silk fibroin complexes. The authors found that CuN x –CNS SAzymes with a CuN 4 structure exhibited superior multienzyme activity (POD-, OXD- and CAT-like) than those with a CuN 2 structure.…”
Section: Non-noble Metal Single Atom Nanozymesmentioning
confidence: 99%
“…Presently, for the treatment of deep wounds, numerous recently developed antibacterial particles, including nanoenzymes and a combination of photothermal therapy and simulated enzyme catalysis, exhibit outstanding antibacterial effectiveness and tissue repair capabilities. [18][19][20] In contrast to certain metallic or precious metal nanoenzymes, the preparation process for CaO 2 -Cu 2 O does not necessitate any specialized equipment, resulting in lower costs while still achieving desirable therapeutic effects.…”
Section: Introductionmentioning
confidence: 99%
“…Micromotors are artificial microdevices that can realize autonomous movement through energy conversion. To meet the requirement of different applications, micromotors in copious morphologies have been devised with diverse propulsion mechanisms. Among them, NIR-II light (1000–1700 nm), which can provide deeper penetration, lower tissue autofluorescence, and photoscattering, has come to the forefront as an emerging external stimulus to drive micromotors to move autonomously in vivo. In contrast, pollen grains, which are nature-derived microscale particles, are identified as an ideal carrier for drug delivery because their special architecture with an inner hollow cavity and porous surface endows them with high cargo-loading capacity. Besides, their spiny structure on the surface endows them with a large area for contacting, thus enhancing their property for adherence. Therefore, it is conceived that an outstanding kind of active adhesive delivery system can be developed for efficient gastrointestinal drug delivery by combining micromotors, NIR-II light, and pollen.…”
Section: Introductionmentioning
confidence: 99%